Effect of COVID-19 on Hair Diseases Observed by Health Care Providers: Analysis of 513 participants - Ecem Bostan; Aysel Cakir (Mattioli1885, 2023)
Introduction: Covid-19 pandemic has been shown to have major acute and chronic impacts on the skin. Various studies, reported that there has been an increase in the number of patients who referred to the outpatient dermatology clinics with the complaint of variable hair diseases, during the era of Covid-19. Hair seems to be substantially affected by both the infection itself and anxiety/stress provoked by the pandemic. Therefore, understanding the impact of Covid-19 on the clinical course of variable hair diseases, has become a major concern in dermatology practice. Objectives: To examine the frequency and types of various, both new-onset and ingravescent hair diseases observed in health care providers. Methods: A web-based questionnaire related to the hair diseases seen in health care providers both prior to Covid-19 pandemic and after the start of the pandemic, was formed. The type of both new-onset and pre-existing hair diseases and ongoing hair diseases observed during Covid-19, were questioned. Results: A total number of 513 participants were included in the study. One hundred seventy cases were diagnosed with Covid-19. During Covid-19 pandemic, 228 reported to have at least one hair disease; the most common one being telogen effluvium, followed by hair greying and seborrheic dermatitis. There was statistically significant relationship between the presence of a new-onset hair disease during the pandemic and being diagnosed with Covid-19 (p=0.004). Conclusion: Our study shows that Covid-19 infection has a significant impact upon the emergence of new-onset hair diseases.